Representation of Middle Eastern Islamic Locality in Video Games - Adhitya Mohammad Maheswara; Nur Fatwa (IBDA` : Jurnal Kajian Islam dan Budaya, 2021)
This article analyzes the depiction of Middle Eastern Islamic locality in video games that has a bad image. This research uses qualitative research method and a literature study approach. It reveals the representation of the Arab world and Muslims in video games developing after the September 11 attacks. The representation had significant impacts on Muslims around the world. It can damage the positive image of Islam and Muslims in the world community. The representation of Muslims in video games, such as in Call of Duty: Modern Warfare 2 and Kuma/ War, uses stereotypes in Western societies. Muslims appear to be terrorists and live in a country that seems isolated